Efeito do exercício físico sobre a glicemia de pacientes idosos com diabetes mellitus tipo 2 - Marques, Franciele Zorzo (2012)
The chronic-degenerative diseases prevail among the pathologies that afflict the elderly people. Among the most common of these diseases is the Diabetes mellitus Type 2, which causes great morbid-mortality. Efforts are being spent in order to control the blood glucose levels, which is the main expression of this illness. Facing this perspective, the main objective of this study is to analyze the effects of physical exercise upon the blood glucose levels in old people with Diabetes mellitus Type 2. In a brief period of time, the effects of physical exercise upon the control of blood glucose in old people assisted by the Presidente Vargas Family Health Strategy center in the municipality of São Luiz Gonzaga/RS were studied. In order to verify such information a non-randomized clinic essay, with a non-randomized sample compound of 40 elderly people with Diabetes mellitus Type 2, from both sexes, age 60 or older, was carried out. The group was divided in two, and 20 people diagnosed with diabetes participating in the Intervention group were called to carry out standard physical exercises for four weeks, while the other 20 old people participated in the Control group, in which the patients kept their routine activities. They had been measured marking of the blood glucose markers, blood pressure, heart beats and anthropometric variables (weight, height, abdominal and pelvic circumference, Body Mass Index - BMI and the ratio Waist/Hips RW/H before and after the intervention). The results show an improvement in the blood glucose levels during fasting (p = 0.011), in the glicolized hemoglobin (p = 0.005) and in the patients life quality (p = 0.008) in the ones that were submitted to the intervention, as well as a decrease in body weight (p = 0.058). Based on the findings, the importance of physical exercise in the control of blood glucose and in the life quality of old people suffering from Diabetes mellitus Type 2 is highlighted